Kualitas Hidup Lanjut Usia yang Bekerja di Bandung - Rahmi, Upik (Jurnal Keperawatan 'Aisyiyah, 2017)
Quality of life is an individual's perception of his / her life in society in the context of existing culture and value system related to purpose, expectation, standard, and attention. Quality of life is an important area of concern that reflects the health status and welfare of the population, and there is no exception for elderly. Elderly ages of 45-59 years who began to enter the period the slowly decreasing ability of body tissues. E lderly belong to the age that are still able to work. This study aims to determine the overview quality of life elderly (45-59 years) who works as well as quality of life based on physical domain, psychological domain, social relations domain and environment domain. This study uses quantitative descriptive method. The sampling used were the total sampling and the sample that will be used are working elderly as much as 31 respondents. Data collection techniques used WHOQOL-BREF questionnaire instrument with reliability test (r = 0.66-0,87). The results of data analysis will be presented in the form of frequency distribution table. From the results of research as many as 30 respondents (96.8%) have a good quality of life. Based on the domain, obtained good results on the physical domain as much as 23 respondents (74.2%) and the psychological domain as much as 17 respondents (54.8%) and the result that are good enough on the domain of social relationships as much as 21 respondents (67.7%) and the environment as much as 29 respondents (93.5%). This research is recommended for companies to improve the quality of life of workers especially pre elderly is by way of requiring workers to use PPE and create a schedule for recreation with all workers.